The White House is burning : August 24, 1814 - Sutcliffe, Jane (Charlesbridge, 2014)
Describes the events of August 24, 1814, the day during the War of 1812 that British troops entered Washington, D.C., and proceeded to pillage and burn the nation's capital city, as reflected in first-hand accounts in diaries, journeys, letters, and other communications.